A Rational Sequencing of Anti-Angiogenic Agents as Second-Line Treatment Choice for mCRC Patients Progressing After a Bevacizumab-Based First Line - Sara De Dosso (healthbook TIMES. Oncology Hematology)
A large proportion of patients with metastatic colorectal cancer (mCRC) experience disease progression after first-line treatment with chemotherapy and bevacizumab, an anti-angiogenic agent, as a result of acquired resistance. However, blocking angiogenesis by targeted therapy towards the vascular endothelial growth factor (VEGF) pathway still forms an essential part of the second-line treatment strategy. Although three approved evidence-based choices for angiogenic agents (continuing treatment with bevacizumab, ramucirumab and aflibercept) are currently available in the second line, making the most effective choice is challenging due to the lack of studies directly comparing these agents. Moreover, despite huge investigational efforts, no predictive biomarker for anti-angiogenic cancer therapies could be identified so far.